Purification and biochemical characterization of fibrino(geno)lytic enzymes from tissues of Antarctic hydrobionts - Raksha, N.; Udovychenko, I.; Halenova, T.; Vovk, T.; Savchuk, O.; Ostapchenko, L. (Ukrainian Antarctic Journal, 2020)
Considering the continuing increase of morbidity and mortality rates associated with cardiovascular diseases, the search for novel compounds able to affect the hemostasis system is among the current trends of modern science and pharmacology. Fibrino(geno)lytic enzymes because of their role in dissolving blood clots as well as prevention of their formation attract special attention. The main goal of the current research was to develop the methodological approaches to obtain fibrino(geno)lytic enzymes from Antarctic hydrobionts and study their effects on the functioning of the hemostasis system. A complex approach which included affinity chromatography and size-exclusion chromatography was applied to isolate the fibrino(geno)lytic enzymes from the tissue of Antarctic nemertea (Parborlasia corrugatus), Antarctic sea urchin (Sterechinus neumayeri), and Antarctic sea star (Odontaster validus). The presence of proteolytic activity was monitored by zymographic technique. Fibrin(ogen)olytic activity was assessed by incubation of the samples with fibrinogen followed by 10% SDS-PAGE analysis. To test the substrate specificity of the enzymes, the chromogenic substrates such as H-D-Phe-Pip-Arg-pNA, pyroGlu-Pro-Arg-pNA, H-D-Val-Leu-Lys-pNA and Bz-IIe-Glu(γ-OR)-Gly-Arg-pNA were used. The influence of fib rino(geno)lytic enzymes on platelet aggregation was assessed in platelet-rich plasma. To analyze the effect of the fibrino(geno)lytic enzymes on coagulation the blood coagulation time was assessed. The obtained results clearly indicated the presence of enzymes with activity toward fibrinogen in the tissues of tested hydrobionts. Based on the results of SDS-PAGE and zymography the molecular weight of the fibrino(geno)lytic enzymes was in the range of 26–34 kDa. The fibrinogen cleavage pattern analyzed by SDS-PAGE revealed the susceptibility of fibrinogen chains to degradation by enzymes from tissues of Antarctic hydrobionts. The fibrino(geno)lytic enzymes from all tested hydrobionts cleaved preferentially the Aα-chain and more slowly the Bβ-chain of fibrinogen. The fibrino(geno)lytic enzymes mediated the significant prolongation of blood clotting time in chronometric tests and inhibition of ADP-induced platelet aggregation. The enzymes exhibit activity against chromogenic substrates, which was more expressed in case of pyroGlu-Pro-Arg-pNA — a specific synthetic substrate for activated protein C and factor XIa. The enzymes isolated from the tissues of Antarctic marine hydrobionts possess a fibrin(ogen)olytic activity and can be of medical interest as therapeutic agents in the treatment and prevention of thrombotic disorders.